Phospholipase Cγ2 Signaling Cascade Contribute to the Antiplatelet Effect of Notoginsenoside Fc - Liu, Yingqiu; Liu, Tianyi; Ding, Kevin; Liu, Zengyuan; Li, Yuanyuan; He, Taotao; Zhang, Weimin; Fan, Yunpeng; Ma, Wuren; Cui, Li; Song, Xiaoping (Frontiers in Pharmacology, 2018)
Scope: Bleeding, the main drawback of clinically used chemical anti-thrombotic drug is resulted from the unidirectional suppression of platelet activity. Therefore, dual-directional regulatory effect on platelet is the main preponderance of Panax notoginseng over these drugs. The dual-directional regulatory effect should be ascribed to the resourceful Panax notoginseng saponins (PNS). Clarifying the mechanism of main PNS in both inhibiting and promoting platelet aggregation will give a full outlook for the dual-directional regulatory effect. The present study is aimed at explaining the mechanism of Notoginsenoside Fc (Fc), a main PNS, in inhibiting platelet aggregation. Methods: In the in vitro study, after incubating platelets with Fc and m-3M3FBS, platelet aggregation was triggered by thrombin, collagen or ADP. Platelet aggregation was measured by aggregometer. Phospholipase Cγ2 (PLCγ2) and protein kinase C (PKC) activities were studied by western blotting. Diacylglycerol (DAG), thromboxane B2 (TXB2) and 1,4,5-inositol trisphosphate (IP3) concentrations were measured by corresponding ELISA kits. Calcium concentrations ([Ca2+]) were estimated through the fluorescence intensity emitted from Fluo-4. In the in vivo study, thrombus model was induced by FeCl3. The effect of Fc on thrombosis was evaluated by measurement of protein content and observation of injured blood vessel. Results: thrombin, collagen and ADP induced platelet aggregation were all suppressed by incubating platelets with Fc. Platelet PLCγ2 and subsequent DAG-PKC-TXA2 and IP3 were down-regulated by Fc as well. However, the basal [Ca2+] in platelet was not altered by Fc. Nevertheless, thrombin triggered activation of PLCγ2 and subsequent DAG-PKC-TXA2 and IP3-[Ca2+] were all abolished by Fc. Fc also attenuated platelet aggregation and PLCγ2 signaling activation induced by PLC activator, m-3M3FBS. In the in vivo study, FeCl3 induced thrombosis in rat femoral artery was significantly alleviated by administration of Fc. Conclusion: The results above suggested the antiplatelet and antithrombotic effects of Fc are carried out through oppression of PLCγ2 and subsequent DAG-PKC-TXA2 and IP3-[Ca2+]. The present study provided theoretical support for new anti-thrombotic drug exploitation by Panax notoginseng.